Readability assessment of the British Association of Dermatologists' patient information leaflets. (1st April 2022) - Hunt, W. T. N.; Sofela, J.; Mohd Mustapa, M. F.; ,; Levell, N. J.; McDonald, B.; Chua, S. L.; Laws, P.; Daunton, A.; Frow, H.; Petrof, G.; Mohd Mustapa, M. F.
Summary: Background: The British Association of Dermatologists (BAD) develops and produces patient information leaflets (PILs) for British clinicians and the general public, and its website provides access to all the PILs. Health literacy across the UK remains variable. Readability instruments assess the comprehensibility of text, predominately using a composite of sentence length and/or word‐syllable number. Instruments usually report text readability categorized by United States (US) grades; ideally, health literature should be rated at US grade ≤ 6 (UK Year 7; age 11–12 years). Methods: In collaboration with the BAD, PILs on the BAD website ( n = 203) were downloaded for readability assessment. PILs were processed prior to analysis using Readability Studio software (Oleander Software, Vandalia, OH, USA). Established readability metrics were used: Flesch–Kincaid (FK), Simple Measure of Gobbledygook (SMOG), Gunning fog index (GFI), Fry, FORCAST and Flesch Reading Ease (FRE). Results: The mean (95% CI) US grade levels for all BAD PILs were: 9.8 (9.7–10.0) for FK, 12.1 (12.0–12.3) for SMOG, 11.8 (11.6–11.9) for GFI, 11.5 (11.1–11.8) for Fry and 10.7 (10.6–10.8) for FORCAST. For FRE, the level is reported from a normal spectrum of 0–100, and was found to be 52.2 (95% CI 34.0–78.0) in this study. In the UK context, the mean readability levels of the BAD PILs were rated as Year 10 (age 14–15 years) for FK and Year 13 (aged 17–18 years) for SMOG. For FK, outputs, only 1.0% of PILs (2 of 203) were the recommended US grade ≤ 6 according to FK, and for SMOG rating, none was rated at this level. Discussion: The majority of BAD PILs have been written at a level that will be challenging for some patients to read. Reducing sentence length and aiming for shorter words will improve accessibility. Abstract : Using six readability instruments, this study assessed the readability of the British Association of Dermatologists' (BAD) patient information leaflets (PILs). The readability measures ascertained that most PILs provided by the BAD are written at a level that may not be comprehensible to a proportion of patients. We compare these findings to the literature and highlight methods for the BAD Clinical Standards Unit to improve readability for future PILs.